نسق الفحولة في رواية ذكر شرقي منقرض ل محمد طه - حماده, حمزة; غنبازي, عبد الحكيم; لخياري, عبد الكريم; شاشة, محمد (University of Eloued جامعة الوادي, 2024)
فرضت الرواية الحديثةُ و المعاصرة نفسها فرضًا في النصوص الأدبية و النّقدية ، و ما ساعدها في ذلك تطور النقد الثقافي الذي أضحى بديلاً عن النقد الأدبي كونه يملك آليات كشف الأنساق الفاعلة في النص الأدبي المعلنة و المضمرة على حدٍ سواء و على اختلاف اتجاهاتها الدينية و الاجتماعية و النفسية..... و حاولنا في بحثنا المتواضع هذا كشف الأنساق حيث قسمنا عملنا الى فصلين الأول نظريًا شاملًا لأهم المفاهيم الخاصة بالنقد الثقافي ، أما الفصل الثاني عكفنا فيه على كشف شفرات الأنساق الثقافية انطلاقًا من نسق العتبات الى النسق النفسي و الدينى و الفحولي ،و التي حاول محمد طه أن يثبت وجوده في الإبداع الأدبي ، كما فرض وجوده في مجال الطب النفسي. The modern and contemporary account imposed itself in literary and monetary texts, which helped it to develop cultural criticism, which has become a substitute for literary criticism, because it has the mechanisms to detect the active patterns of both the declared and the intellect of the literary text and its different religious, social and psychological orientations... In our humble search, we tried to reveal the patterns, where we divided our work into two chapters, theoretically covering the most important concepts of cultural criticism. The second chapter, we worked on the ciphering of cultural patterns, from the lines of thresholds to the psychological, religious and anthropological patterns, in which Muhammad Taha tried to prove his existence in moral creativity, as well as his presence in the field of psychiatry.
دراسة من منظور النقد الثقافي
813/009
Keywords: : نسق الفحولة، ذكر شرقي منقرض، محمد طه، النقد الثّقافي; masculinity system; extinct oriental male; Muhammad Taha; cultural criticism.